KOMODIFIKASI WACANA SENSITIF GENDER FIRZA HUSEIN DI MEDIAINDONESIA.COM - Prayogi Haro Rajagukguk; Chelsy Yesicha (Jurnal Riset Komunikasi (JURKOM), 2019)
The coverage of sensational conversations in the context of pornography between Rizieq Shihab and Firza Husein became interesting to be exploited by the media with a tendency to focus on female actors rather than male actors. On the other side, the media is also careful to package the news according to their interests. The researcher chose Mediaindonesia.com as an object of study that helped publish the news stories about pornography Firza Husein throughout 2017. The purpose of this study was to find out MediaIndonesia.com positioned women in the news discourse and the commodification process formed in the discourse. This research uses qualitative research methods using Sara Mills discourse analysis. Data collection techniques used are documentation, observation and interviews. The subjects involved in this study were MediaIndonesia.com. The unit of analysis of the data taken is 5 news by using pusposif based on google analytics. The results of the study show Firza Husein to be the object to be discussed and the Police become the narrator, then Rizieq Shihab is shown as a victim of slander. Commodification of content seen is news raised from a legal point of view, workers who are involved in totality in digging information, then audiences are harassed to advertisers with invitation adverts and government adverts categories that are displayed in the form of special news columns.